2019
DOI: 10.1002/elsc.201900075
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of laccase onto modified PU/RC nanofiber via atom transfer radical polymerization method and application in removal of bisphenol A

Abstract: In this study, 2‐hydroxyethyl methacrylate (HEMA) was used as the monomers for surface grafting on electrospun PU/RC nanofiber membrane via atom transfer radical polymerization (ATRP) method, and the PU/RC‐poly(HEMA) nanofiber membrane was investigated as a carrier for LAC. Free and immobilized LAC was characterized, and efficiency of bisphenol A (BPA) removal was determined. The results indicated that the PU/RC‐poly(HEMA)‐LAC showed relatively higher pH stability, temperature stability, and storage stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Comparable results were pointed out by Zdarta et al in the degradation studies of naproxen and diclofenac using laccase immobilized in electrospun nanofibers (Zdarta et al 2019). The results given by Li et al (2019aLi et al ( , 2019b) also exhibited that immobilization of laccase onto modified PU/RC (polyurethane-RC/2-hydroxy methacrylate) nano fiber improves the reusability in the removal of bisphenol A. In another report, leaching of immobilized carbonic anhydrase from polylactic acid nanofibrous membranes modified by graphene oxide was found to be less due to steady covalent bonds formed between the enzyme and the support (Sahoo et al 2015).…”
Section: Reusabilitymentioning
confidence: 60%
See 1 more Smart Citation
“…Comparable results were pointed out by Zdarta et al in the degradation studies of naproxen and diclofenac using laccase immobilized in electrospun nanofibers (Zdarta et al 2019). The results given by Li et al (2019aLi et al ( , 2019b) also exhibited that immobilization of laccase onto modified PU/RC (polyurethane-RC/2-hydroxy methacrylate) nano fiber improves the reusability in the removal of bisphenol A. In another report, leaching of immobilized carbonic anhydrase from polylactic acid nanofibrous membranes modified by graphene oxide was found to be less due to steady covalent bonds formed between the enzyme and the support (Sahoo et al 2015).…”
Section: Reusabilitymentioning
confidence: 60%
“…At present nanofibers are used as substrates for enzyme immobilization. Previous research has shown that enzymes immobilized on electrospun materials have higher activity than their unimmobilized counterparts (Li et al 2019a(Li et al , 2019b. Also recent studies have utilized polyvinyl pyrrolidone as spinning agent to produce magnetite PVP composite to form magnetic nano fiber composite for catalyst immobilization purposes (Tomasz & Andrea 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the fabrication of nanofiber mat is also simple when compared to other nanomaterials. The effectiveness of laccase immobilization on nanofiber mat has been proven in various applications and reported in previous studies such as degradation of chlortetracycline, 10 removing bisphenol A 11 and detoxifying hazardous materials. 12 PET is an inexpensive polymer with good structural, thermal, and mechanical properties.…”
Section: Introductionmentioning
confidence: 94%
“…Therefore, laccase has attracted growing interest for various applications including food processing [ 27 ], wastewater treatment [ 28 , 29 ], and biodegradation [ 30 ]. Different types of electrospun fiber membranes, such as an electrospun nylon fiber mat (NFM) [ 26 ], electrospun poly (acrylonitrile-co-styrene/pyrrole) nanofibers, [ 31 ], polyacrylonitrile/montmorillonite (PAN/O-MMT) nanofibers [ 32 ], and polyurethane/regenerated cellulose- poly (2-hydroxyethyl methacrylate) (PU/RC -poly (HEMA)) nanofiber membranes [ 33 ], have been used as supports for laccase immobilization. However, most of these fiber membranes are produced from synthetic polymers, which are difficult to be degraded, thus causing severe pollution issues for the natural environment and potential health concerns for human beings.…”
Section: Introductionmentioning
confidence: 99%